Determinan Produktivitas dan Pendapatan Pengrajin Industri Kerajinan Dulang Kayu di Desa Tembuku Kabupaten Bangli - Wahyuni, Kadek Eka; Arka, Sudarsana (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the direct impact of capital, business duration, labor, technology, and productivity on the income of craftsmen in the wooden tray craft industry in Tembuku Village, as well as to analyze the indirect impact of capital, business duration, labor, and technology on income through the productivity of craftsmen in the wooden tray craft industry in Tembuku Village. The sample size used in this study was 64 craftsmen from the wooden tray craft industry in Tembuku Village, using the proportionate stratified random sampling technique. This study employed path analysis techniques to analyze direct and indirect effects. Based on the path analysis, the research findings conclude that the variables of capital, business duration, labor, and technology have a positive and significant impact on the productivity of craftsmen in the wooden tray craft industry in Tembuku Village, Bangli Regency. The variables of capital, business duration, labor, technology, and productivity have a positive and significant impact on the income of craftsmen in the wooden tray craft industry in Tembuku Village, Bangli Regency. The research findings indicate that productivity mediates the impact of capital, business duration, labor, and technology on the income of craftsmen in the wooden tray craft industry in Tembuku Village, Bangli Regency.